Mechanical alloying of bronze with aluminum and nickel: Impact on corrosion resistance and hardness - Qanita Tayyaba; Adnan Qayyum Butt; Tayyab Ali khan; Zeeshan Nazar; Abdul Rehman; Wu Yusheng (Journal of Alloys and Metallurgical Systems)
The effect of alloying bronze with aluminum (Al) and nickel (Ni) on hardness and corrosion resistance is examined in this work. Bronze alloys were manufactured in vacuum induction melting (VIM) using 99.9 % pure copper as the main component. High-purity tin, aluminum, and nickel were added. This study examined the corrosion behavior of an Al and Ni-modified bronze alloy in a 3.5 % NaCl solution using potentiodynamic polarization (PDP) and electrochemical impedance spectroscopy (EIS). The corrosion resistance of the alloys was assessed, with findings indicating that Ni-bronze had the best corrosion resistance—nearly twice as much as bronze. Microstructural examinations and Rockwell hardness testing further revealed that nickel-bronze had the highest hardness values, owing to strong nickel intermetallic phases formed. This thorough analysis highlights how Ni-bronze alloys perform better in challenging conditions, which qualifies them for uses needing strong mechanical durability and resistance to corrosion.